2022
DOI: 10.3390/ijerph19169952
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Exercise Program for Sarcopenia in Older Adults: The Effectiveness of Explainable Artificial Intelligence-Based Clinical Assistance in Assessing Skeletal Muscle Area

Abstract: Background: Sarcopenia is a geriatric syndrome characterized by decreased skeletal muscle mass and function with age. It is well-established that resistance exercise and Yi Jin Jing improve the skeletal muscle mass of older adults with sarcopenia. Accordingly, we designed an exercise program incorporating resistance exercise and Yi Jin Jing to increase skeletal muscle mass and reverse sarcopenia in older adults. Additionally, machine learning simulations were used to predict the sarcopenia status after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Generally speaking, skeletal muscle mass represents a crucial of strength, endurance, and physical performance. A previous 24-week combined resistance exercise and Yi Jin Jing had a positive effect on increasing skeletal muscle mass and delaying sarcopenia in the elderly [ 21 ], which confirmed our results findings.…”
Section: Discussionsupporting
confidence: 90%
“…Generally speaking, skeletal muscle mass represents a crucial of strength, endurance, and physical performance. A previous 24-week combined resistance exercise and Yi Jin Jing had a positive effect on increasing skeletal muscle mass and delaying sarcopenia in the elderly [ 21 ], which confirmed our results findings.…”
Section: Discussionsupporting
confidence: 90%
“… 145 Furthermore, Wei et al conducted a study in which they combined RT with Yijin Jing exercises in elderly patients with sarcopenia. 146 Their findings indicated that this combined exercise regimen resulted in improved muscle area compared to RT alone and the control group.…”
Section: Other Non-pharmacological Strategiesmentioning
confidence: 97%
“…There is growing evidence that telemedicine in cardio-oncology is effective and well tolerated, even in older patients. 105–107 Telemedicine approaches are effective and safe in older cancer patients, with increasing use of artificial intelligence. 108–110 However, patients’ social skills and social networks, especially in the last decades of life and in independent patients, need to be carefully assessed.…”
Section: Core Effectivenessmentioning
confidence: 99%